Job satisfaction, organizational commitment and stress among offshore oil and gas platform employees - Harun, H. (Canadian Center of Science and Education, 2014)
Working offshore on an oil rig is perceived as a challenge to many people. Having to live and work at the same site, shift-work schedule with long working hours, high risks and remote work environment; are some common features of an offshore job. High job satisfaction (JS), strong organizational commitment (OC) and minimal stress (St) are key factors to retain the offshore oil and gas platform employees. This is critical to oil and gas companies as skilled and experienced employees are highly demanded in the industry. This study aimed to examine the level of job satisfaction, organizational commitment and stress among oil rig employees (n=214) situated in the coast of East Malaysia. This study also analyzed the relationship between the three variables. The data was collected using a self-administered questionnaire. The findings suggested a moderate level of stress and job satisfaction, while organizational commitment was found to be quite high among the respondents. Job satisfaction was found to have significant positive association with organizational commitment, on the other hand stress was found to be negatively correlated to OC & JS. The implications of these findings for practice and theory in the field of Human Resource Management are discussed.